Analysis of Monomer Elution from Bulk-fill and Nanocomposites Cured with Different Light Curing Units Using High Performance Liquid Chromatography - Hurmuzlu, Feridun; Kilic, Vahti (Technical Assoc Photopolymers,Japan, 2020)
The aim of this study was to investigate the effect of different light curing units and light modes on the amount of residual monomers eluted from different resin-based composites. Initially, a total of 96 composite samples (N=24/group) were prepared from 3 bulk-fill composites with different characteristics and a nanohybrid composite using a mold (diameter: 5 mm, height: 4 mm). Then, each group was divided into 4 subgroups (n=6). Polymerization of the resin composites was performed using a halogen light source (Hilux 250), a 2nd generation LED device (Elipar DeepCure -S) and a 3rd generation LED device (Valo, standard and ultra modes). Samples were stored in 75% ethanol solution and residual monomers eluted in the solution were analyzed with HPLC after 1 day and 1 month. Monomer concentrations corresponding to the peak areas in chromatograms were calculated in ppm to obtain data for statistical analysis. The study data were analyzed using One Way ANOVA (p=0.05) and post-hoc Tukey tests. The type of the light-curing unit significantly affected the amount of residual monomer released in all composite groups (p<0.05). Except the Fill-Up composite groups, the least monomer elution was detected in the groups cured with Elipar DeepCure-S. Residual monomer amounts detected after 30 days were significantly increased in comparison to those eluted after 1 day in all groups. In light of these findings, it was concluded that the light curing units might have an impact on the monomer elution from different composites.
Keywords: Bulk-fill composite; Light curing units; Photopolymerization; HPLC; residual monomer